Day 2 Tue, September 01, 2020 2020
DOI: 10.2118/200408-ms
|View full text |Cite
|
Sign up to set email alerts
|

Bhagyam ASP Pilot: Successful Formulation Development to Pilot Design and Planning

Abstract: The paper discusses the alkaline surfactant polymer (ASP) flood pilot design including formulation development, pilot area selection, well and pattern type, slug size and sequence, slug viscosity etc for the Bhagyam field. It also discusses the various lab, well and reservoir surveillance techniques planned for the baseline, ASP flood monitoring, residual oil saturation and incremental recovery estimates from the pilot. The Bhagyam is an onshore field in the Rajasthan state of western India and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Various surveillance methods are discussed in Volokitin et al's report. Jain et al 2020 reported the pilot design of ASP flooding for an onshore field in India. Their report includes chemical formulation development, pilot area selection, well and pattern type, slug size and sequence, slug viscosity, etc.…”
Section: Application Of Artificial Intelligence For Ceor Operationmentioning
confidence: 99%
“…Various surveillance methods are discussed in Volokitin et al's report. Jain et al 2020 reported the pilot design of ASP flooding for an onshore field in India. Their report includes chemical formulation development, pilot area selection, well and pattern type, slug size and sequence, slug viscosity, etc.…”
Section: Application Of Artificial Intelligence For Ceor Operationmentioning
confidence: 99%
“…Although ASP flooding seems promising in the laboratory as a tertiary recovery method, field experience has revealed several complicating features of the technology. Thus, it has been observed that the main problems while ASP flooding is related to operational arrays [12][13][14][15]. The scaling problem is the most common among ASP flood projects, and it creates the need to redesign surface facilities from ASP solution preparation units to production and processing units.…”
Section: Chemical (Asp) Flood Risks and Feasibility Assessmentmentioning
confidence: 99%
“…The main associated problem is the loss of production. Therefore, potential emulsification issues should be envisaged preliminary as it was done in the Bhagyam field having additional demulsifier injection wells near producers [12]. Also, Finol et al [13] have reported preliminary laboratory experiments on identifying cost-effective demulsifiers in the designing stage of the Al Khalata pilot test.…”
Section: Chemical (Asp) Flood Risks and Feasibility Assessmentmentioning
confidence: 99%
See 1 more Smart Citation